Penerapan Metode Regresi Linear Berganda Dalam Prediksi Jumlah Pemakaian Obat Pada Rumah Sakit Rafflesia Kota Bengkulu - Aryo Sumirso Wahyudi; Khairil Khairil; Ricky Zulfiandry (UNIVED Press, 2024)
Rafflesia Hospital Bengkulu is one of the hospitals are in Bengkulu City. The purpose of this study is to provide information on the results of predicting the amount of drug usage, as a benchmark in drug management at Rafflesia Hospital Bengkulu City. The implementation of Multiple Linear Regression Method in predicting the amount of drug usage at Rafflesia Hospital Bengkulu City can help provide information on the predicted results of drug usage in the following month and can be used as an evaluation material and illustration for planning drug purchases to be made by Rafflesia Hospital Bengkulu. Based on data test from 5 (five) drugs, the results of predicting the amount of drug usage using the Multiple Linear Regression Method have a good level of accuracy from the test results in the Prediction Month of February and Prediction Year in 2024. Whereas, the prediction of drug usage amount is aqua 25ml as much as 630, aminofluid 500/bfluid as much as 8, aqua water irrigation as much as 189, aqua l liter as much as 91, and aqua 250ml as much as 33.